Localisation of the unerupted maxillary canine: further observations - Jacobs Stanley G. (Sciendo, 1998)
This paper discusses the interpretation of radiographs taken to localise impacted maxillary canines. In particular, the sometimes unexpected radiographic appearance of labially impacted canines is explained.